Strong Small‐Scale Differentiation but No Cryptic Species Within the Two Isopod Species Asellus aquaticus and Proasellus coxalis in a Restored Urban River System (Emscher, Germany) - Martina Weiss; Armin W. Lorenz; Christian K. Feld; Florian Leese (Ecology and Evolution)
ABSTRACT Worldwide, humans have strongly altered river networks. Key changes resulted in modified hydromorphology, poor habitat quality and availability, migration barriers, and pollution. Restoration measures aim at mitigating anthropogenic stressors and at restoring connectivity, but the biological success of these measures is not guaranteed. Analyzing genetic diversity and metapopulation structure of target species in the river network with genetic markers can help to understand recolonization processes and to identify persisting gene flow barriers. Here, we studied the population genetic structure of the two pollution‐tolerant detritivorous isopod species, Asellus aquaticus and Proasellus coxalis, in the former heavily degraded and polluted, but now mostly restored Emscher catchment in Germany. For both species, we analyzed mitochondrial cytochrome c oxidase I (COI) gene sequences and nuclear genome‐wide single nucleotide polymorphism (SNP) data. Surprisingly, we found a strong metapopulation structure for both species with several isolated populations on a small‐scale of few kilometers, but a still high genetic diversity, especially in the COI gene. For both taxa, potentially cryptic species are known, but our SNP data showed that the mitochondrial lineages represent only one species, each, in the study area. This highlights the importance of integrating high‐resolution nuclear markers into species identification because species diversity may otherwise be overestimated. While we could identify some migration barriers and find indications for passive dispersal by birds or humans, these factors could not fully explain the local metapopulation structure, suggesting that also other drivers, such as isolation by adaptation, priority effects, or biotic interactions, play a role in shaping the population genetic structure.